Geometry Textbook Development Based on Gorontalo Local Wisdom for Elementary School Students - Huljannah, Miftha; Yahiji, Kasim; Anwar, Herson (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2024)
The current use of geometry textbooks in elementary schools still focuses on abstract theories and concepts, adhering to national standards that do not always align with local cultural characteristics. The development of a geometry teaching material based on the local wisdom of Gorontalo was chosen as one of the solutions to this issue. This research and development utilized the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were fourth, fifth, and sixth-grade students and teachers at MIT Al-Ishlah and SDN 3 Bulango Ulu. Data were collected through evaluation tests, expert validation questionnaires, and questionnaires for teachers and students. The results of the validation by content experts, language experts, and media experts were 78.4%, 83.33%, and 94.64%, respectively, all categorized as